A thermosensitive gel system based on probiotic extracellular vesicles to treat vulvovaginal candidiasis co-infected with bacteria - Yameng Wang; La Ta; Jingying Zhang; Qibin Li; Yangjun Feng; Keyun Wang; Mengjie Wang; Xiaoyi Yu; Peige Zhao; Xue Ke (Chemical Engineering Journal, 2026)

Predictive, preventive, and personalized medicine for respiratory viral infections: Integration of mechanistic insights and precision interventions - Ousman Bajinka; Lamarana Jallow; Xiaoxia Feng; Yangjun Zhang; Na Li; Xianquan Zhan (Next Research, 2026)

Artesunate attenuates pulmonary fibrosis by suppressing fibroblast senescence through inhibition of the STAT3/p53 signaling pathway - Jianyi Ding; Zhile Chen; Jiaqin Yu; Yangjun Xu; Ting Zhu; Bin Wang; Zhuyang Feng; Xinhuo Li; Xiumin Qian; Bingqian Jin; Guangmao Yu; Chu Zhang; et al. (Toxicology and Applied Pharmacology, 2026)

Spatio-temporal distribution and source analysis of nutrients and antibiotics in the waters of a mariculture area in Haizhou Bay, Yellow Sea - Liyuan Wang; Wei Jin; Siqi Xie; Shuo Wang; Ruilin Zhang; Dong Xue; Yangjun Chen; Xinran He; Zhihua Feng (Regional Studies in Marine Science, 2024)

Designing regional joint prevention and control schemes of PM2.5 based on source apportionment of chemical transport model: A case study of a heavy pollution episode - Yangjun Wang; Miao Ning; Qingfang Su; Lijuan Wang; Sen Jiang; Yueyi Feng; Weiling Wu; Qian Tang; Shiyu Hou; Jinting Bian; Ling Huang; Guibin Lu; et al. (Journal of Cleaner Production, 2024)

Accumulation of microplastics in the marine sediments of the Chukchi Sea, Arctic Ocean - Tao Zhang; Wenkang Yang; Silu Pang; Xihua Cao; Yangjun Chen; Mohamed Seif; Peng Ren; Yanguang Liu; Zhihua Feng (Regional Studies in Marine Science, 2024)

Bioaccumulation characteristics of typical pollutants in seafood from coastal waters of Jiangsu, China - Yangjun Chen; Xueting Chen; Rendong Jiang; Shihu Li; Xiaona Ma; Yixin Sun; Tao Zhang; Zhihua Feng (Continental Shelf Research, 2023)

Pollution concerns in mariculture water and cultured economical bivalves: Occurrence of microplastics under different aquaculture modes - Kexin Song; Rui Wang; Guang Yang; Siqi Xie; Yangjun Chen; Feifei Yang; Wei Huang; Tao Zhang; Zhihua Feng (Journal of Cleaner Production, 2023)

Underestimation of biomass burning contribution to PM2.5 due to its chemical degradation based on hourly measurements of organic tracers: A case study in the Yangtze River Delta (YRD) region, China - Qing Li; Kun Zhang; Rui Li; Liumei Yang; Yanan Yi; Zhiqiang Liu; Xiaojuan Zhang; Jialiang Feng; Qiongqiong Wang; Wu Wang; Ling Huang; Yangjun Wang; et al. (Science of The Total Environment, 2023)

Microplastics in commercial clams from the intertidal zone of the South Yellow Sea, China - Ruikai Tang; Tao Zhang; Kexin Song; Yixin Sun; Yangjun Chen; Wei Huang; Zhihua Feng (Frontiers in Marine Science, 2022)
Clams are commercially important species and are a vital component of the offshore ecosystem. Investigations on microplastics (MPs) in clams have attracted public attention recently, for its ecological and food safety risks. However, knowledge gaps still exist regarding MPs in commercial clams from the intertidal zone of the South Yellow Sea (SYS), China, an important clam habitat. In this study, to investigate the distribution of MPs in clams of the SYS, four species of clams were collected from nine sites in different tide zones (high, middle, and low tides) in three coastal areas (Nantong, Yancheng and Lianyungang). The abundance and characteristics of MPs, including size, shape, color and composition, were determined using microscope and micro-Fourier transform infrared (FTIR) spectroscopy. Furthermore, to evaluate the MPs purification ability of clams, the abundance of MPs in various tissues was examined by microscopic observation after being purified in filtered seawater for 72 h. The results showed that there were significant differences in the abundance of MPs in clams from different regions, with the most serious pollution in the high-tide zone. Moreover, the lowest MPs abundance was found in Yancheng (5.07 ± 2.73 items/individual, 1.16 ± 0.78 items/g), while Lianyungang was found with the most abundant MPs (7.52 ± 2.68 items/individual, 3.94 ± 3.00 items/g). The size of MPs in Ruditapes philippinarum (1,329.99 μm) was significantly higher than in other species. The MPs in clams were characterized by fiber in shape, black-grey, blue-green and white-transparent in color and rayon in composition. Moreover, it was found that the MPs originally present in various tissues tended to migrate and accumulate into the mantle of the clam during depuration, and after 72 h of depuration, removing the mantle could reduce nearly half amount of microplastics in clams. Overall, our study revealed the microplastic distribution in commercial clams from the intertidal zone of the SYS and provided suggestions for the safety of aquatic production.